Temples of the Earthbound Gods Stadiums in the Cultural Landscapes of Rio de Janeiro and Buenos Aires - Gaffney, Christopher Thomas (University of Texas Press, 2021)
In Rio de Janeiro, the spiritual home of world football, and Buenos Aires, where a popular soccer club president was recently elected mayor, the game is an integral part of national identity. Using the football stadium as an illuminating cultural lens, Temples of the Earthbound Gods examines many aspects of urban culture that play out within these monumental architectural forms, including spirituality, violence, rigid social norms, anarchy, and also expressions of sexuality and gender. Tracing the history of the game in Brazil and Argentina through colonial influences as well as indigenous ball courts in Mayan, Aztec, Zapotec, Mixtec, and Olmec societies, Christopher Gaffney's study spans both ancient and contemporary worlds, linking the development of stadiums to urbanization and the consolidation of nation building in two of Latin America's most intriguing megacities